2015
DOI: 10.5935/0104-7795.20150001
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the "Life Space Assessment - LSA" Questionnaire in a group of hemiplegic patients

Abstract: The mobility of a hemiplegic patient is an interaction between their functional ability and external factors. The "Life Space Assessment" (LSA) questionnaire is a tool that assesses their mobility on 5 levels. Objective: To validate the LSA in a population of stroke survivors in physical therapy at a rehabilitation center, correlating it with measures of physical performance. Method: Instruments used in concurrent validation: Timed Up and Go Test (TUG), Postural Assessment Scale (PASS), Rivermead Mobility Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
(16 reference statements)
1
10
0
Order By: Relevance
“…The need for further study of the clinical applications of LSA has been noted; 28 this study enhances that small body of work, and is the first study of LSA in a United Kingdom setting. Our findings are consistent with those from the most robust clinical population studies in terms of the construct (difference between groups) 35 , 41 , 44 , 45 , 50 and convergent 26 , 33–36 , 38 , 39 , 44 validity, responsiveness over treatment, 41 , 42 , 44 , 45 and absence of floor/ceiling effects 36 , 39 of LSA. A particularly important feature of our findings is that they occurred in the context of a median baseline LSA score of 20, which is lower than any reported in the literature, and far below the range (≤ 52–56) that has been proposed 28 , 33 as the “cutoff score” indicating mobility problems sufficient to hinder activities of daily living.…”
Section: Discussionsupporting
confidence: 90%
“…The need for further study of the clinical applications of LSA has been noted; 28 this study enhances that small body of work, and is the first study of LSA in a United Kingdom setting. Our findings are consistent with those from the most robust clinical population studies in terms of the construct (difference between groups) 35 , 41 , 44 , 45 , 50 and convergent 26 , 33–36 , 38 , 39 , 44 validity, responsiveness over treatment, 41 , 42 , 44 , 45 and absence of floor/ceiling effects 36 , 39 of LSA. A particularly important feature of our findings is that they occurred in the context of a median baseline LSA score of 20, which is lower than any reported in the literature, and far below the range (≤ 52–56) that has been proposed 28 , 33 as the “cutoff score” indicating mobility problems sufficient to hinder activities of daily living.…”
Section: Discussionsupporting
confidence: 90%
“…There have been a few studies assessing the life-space in stroke patients. Estima et al [ 5 ] examined the validity of life-space assessment in Brazilian stroke patients and the interaction between their functional ability and external factors. Unlike our study, the inclusion criterion was having been diagnosed with only hemiplegia caused by stroke and the exclusion criterion was having been diagnosed with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Peel et al [ 3 ] described statistically significant relationships between LSA and traditional measures of physical function, sociodemographic characteristics, depression, and cognitive status in older adults, and Polku et al [ 4 ] reported significant associations between life space and depressive symptoms among older community-dwelling people. A study in Brazil examined post-stroke patients in their life spaces [ 5 ], but there is little research on life space assessment in stroke patients. The relationships between LSA scores in stroke patients and their quality of life (QOL) and post-stroke depression have not been evaluated, although these psychologic and sociodemographic characteristics substantially affect the life space of community-dwelling adults [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mean age of participants was 75 years, ranging from 43 years to 85 years. Studies included community-dwelling older persons without [ 12 , 14 , 15 , 17 20 , 24 , 26 28 , 31 36 , 38 , 39 , 47 , 48 ] and with cognitive impairment [ 21 ], persons with power mobility devices [ 16 ], persons with chronic obstructive pulmonary disease [ 43 – 45 ], persons with stroke [ 40 , 42 ], persons with vestibular disorders [ 37 ], patients with Parkinson disease [ 49 ], persons with spinal cord injury [ 46 ], persons with critical illness [ 29 ], persons in palliative care [ 30 ], geriatric inpatients [ 22 , 23 , 50 ], and nursing home residents [ 13 ]. Construct and concurrent validity, and test-retest reliability were the most frequently evaluated psychometric properties.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 summarizes the results on the psychometric properties and recommendations for each questionnaire based on the 37 included validation studies. Most studies (n = 19) were identified for evaluating the psychometric properties of UAB-LSA [15] in different languages or populations [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], additionally the phone-based [16,46,47] and proxy-reported questionnaires [17] are also based on the UAB-LSA. Detailed information on the individual studies, questionnaires, and COSMIN quality ratings is provided in Table S3.…”
Section: Psychometric Propertiesmentioning
confidence: 99%